ASSESSMENT OF THE TECHNICAL CONDITION OF STEEL–REINFORCED CONCRETE FLOORS OF WORKING TOWERS OF GRAIN STORAGE FACILITIES - Ponomarov, Pavlo Yakovych; Kostyra, Nataliia Oleksandrivna (Theory and practice of design, 2025)
This paper examines the technical condition assessment of steel-reinforced concrete floors in grain elevator working towers through comprehensive inspection methods applied prior to commissioning. The research focuses on evaluating construction quality, identifying defects, and validating structural integrity using advanced non-destructive testing techniques. Particular attention is given to detecting hidden imperfections such as voids, adhesion failures, and early-stage corrosion that may compromise long-term performance and safety under operational dynamic loads from grain cleaning equipment. Purpose. The aim of this study is to develop and apply an integrated approach for assessing the technical condition of steel-reinforced concrete composite floors in elevator separator levels, combining multiple non-destructive testing methods to ensure structural reliability before operational use. Methodology. The study employed a multi-stage inspection program including preliminary project documentation analysis, detailed visual inspection with photographic documentation, and instrumental surveys. Key non-destructive testing methods applied include optical-visual inspection, Schmidt hammer rebound testing for concrete compressive strength evaluation, crack detection and classification, core sampling for laboratory analysis of concrete strength and density, reinforcement corrosion assessment, and infrared thermography for detecting hidden defects and thermal anomalies indicating adhesion failures or material discontinuities. Results. Measurements at twelve control points confirmed concrete slab thickness compliance with design specifications of 150 mm (±5 mm tolerance). Visual inspection identified isolated micro-cracks up to 0.2 mm wide near equipment fastening zones and structural joints. Thermographic surveys detected localized thermal anomalies around Nelson stud connectors, suggesting potential adhesion weaknesses or initial corrosion. Laboratory testing of core samples verified concrete class C25/30 and density approximately 2400 kg/m³, with no significant reinforcement corrosion observed. Overall technical condition was assessed as satisfactory, with localized defects requiring monitoring. Scientific novelty. This work presents an integrated diagnostic methodology combining thermal imaging with traditional non-destructive testing techniques specifically tailored for steel-concrete composite floors in high-vibration industrial environments. Practical relevance. The developed methodology enables informed decision-making regarding maintenance priorities and repair strategies, contributing to enhanced safety, durability, and operational reliability of grain elevator infrastructure. Results provide practical guidelines for quality control during construction and commissioning phases of steel-reinforced concrete floors in agricultural and industrial facilities.